Seeing degree zero : Barthes/Burgin and political aesthetics - Bishop, Ryan, 1959-; Manghani, Sunil; Burgin, Victor (Edinburgh University Press, 2019)
In literature and the visual arts, zero degree represents a neutral aesthetic situated in response to and outside of the dominant cultural order. Starting from Roland Barthes' 1953 book Writing Degree Zero, this volume examines the historical, theoretical and visual aspects of the term in collaboration with artist and writer Victor Burgin.